MENINGKATKAN KECERDASAN LOGIKA MATEMATIKA MELALUI MODEL PEMBELAJARAN EXPERIANTIAL LEARNING - Yulianti, Feny; Zahro, Ifat Fatimah (IKIP Siliwangi, 2020)
Efforts to develop mathematical intelligence in early childhood are needed, besides, to preparing children's social and emotional mental readiness, mathematical logic intelligence as a basis for developing mathematical abilities for readiness to attend basic education. Most of the children have not developed intelligence in mathematical logic, because learning is applied more often using textbooks, the teacher's competence in understanding the potential of children's intelligence is not fully understood, so children are less enthusiastic when learning. The purpose of this study was to determine the application of experiential learning models to improve the intelligence of mathematical logic in children aged 4-5 years. The method used was classroom action research with group A children (4-5 years old). consists of 11 girls and 11 boys in RA Multazam. The data collection techniques used are observation and documentation, the steps being carried out are initial observation, pre-cycle, cycle 1, cycle II, consisting of planning, action, observation, and reflection. Data analysis techniques used by reducing data, displaying data, and drawing conclusions. After being given action in the first cycle through experiential learning, there is a better chance, 4.5% of children begin to develop, 63% develop as expected, 31.8% of children develop very well. Based on the results of the study it can be concluded that through the experiential learning model learning can improve children's mathematical logic intelligence.Upaya pengembangan kecerdasan logika matematika anak usia dini sangat diperlukan, selain menyiapkan kesiapan mental sosial dan emosional anak, kecerdasan logika matematika sebagai dasar pengembangan kemampuan matematika untuk kesiapan mengikuti pendidikan dasar. Sebagian besar anak belum berkembang dalam kecerdasan logika matematika, dikarenakan pembelajaran yang diterapkan jarang menggunakan media,sehingga anak kurang antusias saat belajar. Tujuan dari penelitian ini untuk mengetahui penerapan model pembelajaran experiantial learning untuk meningkatkan kecerdasan logika matematika anak usia 4-5 tahun. Metode yang digunakan adalah Penelitian tindakan kelas (classroom action research) subjeknya anak kelompok A (4-5 tahun) terdiri dari11anak perempuan dan 11 anak laki-laki di RA Multazam. Teknik pengumpulan data yang digunakan adalah observasi dan dokumentasi, tahapan yang dilakukan yaitu observasi awal, pra siklus, siklus 1, siklus II, terdiri dari perencanaan, tindakan, observasi serta refleksi. Teknik analisis data yang digunakan dengan cara mereduksi data, mendisplay data, serta pengambilan kesimpulan. Setelah diberikan tindakan pada siklus I1 melalui pembelajaran experiantial learning maka ada perubahan yang lebih baik, 4,5% anak mulai berkembang, 63% berkembang sesuai harapan, 31,8% anak yang berkembang sangat baik. Berdasarkan hasil penelitian dapat disimpulkan bahwa melalui model pembelajaran experiantial learning dapat meningkatkan kecerdasan logika matematika anak .